Consequences of use of fenpropathrin compared to other fish toxicants in commercial aquaculture (Asian-Australasian Journal of Food Safety and Security, 2019)
Use of fish toxicants is an important management tool in inland commercial aquaculture. In entrepreneurial fishery in northwest Bangladesh where pond ownership (using rights due to lease) changes frequently (every few years) use of fish toxicants is very routine and more crucial. Along with some traditional fish toxicants (rotenone and aluminium phosphide), unconventional and insecticides like fenpropathrin (not approved for aquaculture use) are being used by fish farm owners in northwest Bangladesh. The study was conducted to understand the consequences of use of fenpropathrin compared to other traditional fish toxicants in commercial aquaculture for harvesting of food fish. Of all the toxicants, fenpropathrin’ s impact was lowest on zooplankton and aquatic insect population, while rotenone had the lowest impact on benthos population in terms of killing and quick recovery time for the population, primarily due to the high turbidity (suspended soil particle) of the pond water (under this study) by which both fenpropathrin and rotenone got affected. Aluminium phosphide found to be more damaging in terms of killing and relatively longer recovery time for zooplankton, aquatic insect and benthos population. Using convenience, quick killing, cheaper price, short duration of toxicity and no potential long-term damage of the waterbody contributes positively for fenpropathrin as fish toxicant except the severe potential public health concern from eating of fish killed by fenpropathrin due to very high bioconcentration factor of fenpropathrin; hence, demands regulation of fenpropathrin’ s use as fish toxicants for food fish.Asian Australas. J. Food Saf. Secur. 2019, 3(1), 27-37